An ice‐rich flow origin for the banded terrain in the Hellas basin, Mars. Issue 12 (21st December 2015) - Diot, X.; El‐Maarry, M. R.; Guallini, L.; Schlunegger, F.; Norton, K. P.; Thomas, N.; Sutton, S.; Grindrod, P. M.
Abstract: The interior of Hellas Basin displays a complex landscape and a variety of geomorphological domains. One of these domains, the enigmatic banded terrain covers much of the northwestern part of the basin. We use high‐resolution (Context Camera and High‐Resolution Imaging Science Experiment) Digital Terrain Models to show that most of the complex viscous flowing behavior exhibited by the banded terrain is controlled by topography and flow‐like interactions between neighboring banded terrain. Furthermore, the interior of the basin hosts several landforms suggestive of the presence of near‐surface ice, which include polygonal patterns with elongated pits, scalloped depressions, isolated mounds, and collapse structures. We suggest that thermal contraction cracking and sublimation of near‐surface ice are responsible for the formation and the development of most of the ice‐related landforms documented in Hellas. The relatively pristine form, lack of superposed craters, and strong association with the banded terrain, suggest an Amazonian (<3 Ga) age of formation for these landforms. Finally, relatively high surface pressures (above the triple point of water) expected in Hellas and summertime temperatures often exceeding the melting point of water ice suggest that the basin may have recorded relatively "temperate" climatic conditions compared to other places on Mars. Therefore, the potentially ice‐rich banded terrain may have deformed with lower viscosity and stresses compared to other locations on Mars, which may account for its unique morphology. Key Points: Banded terrain: diversity of ice‐related landforms Flow‐like interactions Near‐surface ice in the deepest part of Mars